Optical polyvinyl alcohol film
Patent Information
- Application Number
- KR1020267018934
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-02-14
- Filing Date
- 2026-02-13
- Publication Date
- 2026-09-01
Smart Images

Figure PCT00001
Abstract
Description
Technology Field
[0001] The present invention relates to an optical polyvinyl alcohol film. Background Technology
[0002] Polarizers, which have the function of transmitting and shielding light, are a basic component of liquid crystal displays (LCDs) along with liquid crystals that change the polarization state of light. LCDs are used in a wide range of applications, including small devices such as electronic desktop calculators and wristwatches, notebook computers, liquid crystal monitors, liquid crystal color projectors, liquid crystal televisions, in-vehicle navigation systems, mobile phones, and measuring instruments used indoors and outdoors.
[0003] Polarizers are generally manufactured by dyeing, uniaxially stretching, and, if necessary, further fixing treatment with a boron compound or the like on a polyvinyl alcohol film (hereinafter, "polyvinyl alcohol" may be abbreviated as "PVA") to produce a polarizing film, and then laminating a protective film, such as a cellulose triacetic acid (TAC) film, onto the surface of the polarizing film. Recently, due to the increasing demand for LCDs, there is a need to efficiently manufacture polarizing films, which are one of the components. To increase the manufacturing efficiency of polarizing films, it is possible to adopt high stretching ratio conditions using a high-temperature solution during the manufacturing of polarizing films. As the stretching ratio increases, there is a possibility that breakage may occur in conventional PVA films during stretching, so there is a need for PVA films with even better stretchability than conventional products.
[0004] Patent Document 1 discloses that if a PVA-based film with a degree of crystallization of 38% or more and a dissolved residue crystallization rate of 18% or less after immersion in water for 30 seconds is used, the elongation during the manufacture of a polarizing film is excellent, which suppresses breakage and allows for the production of a polarizing film exhibiting high polarization performance, and the amount of PVA-based resin leaching when immersed in water can be reduced, thereby preventing contamination of the polarizing film manufacturing equipment. However, this degree of crystallization is determined by using a differential scanning calorimeter (DSC) to increase the temperature from -50°C to 250°C and obtaining the heat of fusion; however, since PVA is a crystalline polymer, crystallization proceeds as the temperature increases in the DSC. Consequently, the baseline required to determine the heat of fusion changes, making it impossible to stably obtain the value of the heat of fusion with good reproducibility. Therefore, it is believed that the initial degree of crystallization of the PVA film, which is used for the stretching process of a polarizer, cannot be evaluated with high reliability from the heat of fusion obtained from DSC. Furthermore, regarding the crystallization rate of the dissolved residue after 30 seconds of immersion, it was obtained by measuring the PVA film after immersion at a water temperature of 10°C for 30 seconds using the solid echo method of NMR, and it is stated that since the crystallization rate of the dissolved residue is 18% or less, breakage due to tension reduction is reduced even during high stretching during the manufacture of the polarizer. However, generally, the manufacturing of polarizers consists of a swelling process, a dyeing process, a crosslinking process, a stretching process, a washing process, and a drying process, and any of these processes are often carried out at a temperature higher than 10°C (for example, the temperature range is 15 to 65°C). Therefore, it is thought that the crystallinity of the dissolved residue after immersion at a water temperature of 10°C for 30 seconds does not sufficiently reflect the crystallization state of PVA during the stretching process. As described above, there is much room for improvement.
[0005] Patent Document 2 discloses that, as a PVA film containing a vinyl alcohol-based polymer, if a PVA film is used in which the relaxation time of component A, measured by the Solid Echo method at 80°C using pulsed NMR, is 0.0083 milliseconds or more and 0.0093 milliseconds or less, and the component ratio of component A is 10% or more and 35% or less, then the polarization performance is good and it is difficult for wrinkles and bonding to occur during the manufacture of a polarizing film. Component A refers to a component with low molecular mobility and a hard component, which is thought to refer to the crystalline component of PVA. However, in Patent Document 2, the stretching ratio during the manufacture of a polarizing film is evaluated to be 5 times, but the stretching ratio currently in the mainstream is stricter at around 5.6 to 6.0 times, and it is unclear whether a polarizing plate can be continuously manufactured under such conditions.
[0006] Patent Document 3 discloses that, as a PVA film comprising a vinyl alcohol-based polymer, a polyvinyl alcohol film after being immersed in water at 60°C for 2 hours is used as a measurement sample, and the NMR signal intensity at the 0.10 millisecond mark measured by the Solid Echo method at 60°C using pulsed NMR is 78% or less of the initial intensity, thereby providing a polarizing film that is difficult to degrade in polarizing performance even under high humidity while maintaining good polarizing performance. Furthermore, it is explained that the NMR signal intensity of the said PVA film significantly decays within a certain period of time even after being placed under high humidity, which means that there is a relatively large amount of hard components with low molecular mobility within the PVA film, and it is inferred that the said PVA film contains a relatively large amount of crystalline components. However, as with Patent Document 2, in addition to the fact that the stretching ratio during the manufacture of the polarizing film is evaluated to be 5 times, it is unclear whether the degree of polarization at the currently required transmittance of 43.5% is 99.99% or higher, so the current performance level cannot be satisfied. Prior art literature
[0007] International Publication No. 2023 / 182249, Japanese Patent Publication No. 2019-184993, International Publication No. 2019 / 189693 The problem to be solved
[0008] The objective of the present invention is to provide a PVA film capable of producing a polarizing film with excellent optical performance, which has no end folding during stretching and does not break even when the stretching ratio is increased to a high magnification. means of solving the problem
[0009] Taking the above situation into account, the inventors carefully examined the matter and found that there is a close relationship between the elongation of each process of the stretching process when manufacturing a polarizing plate and the amount of crystallization of PVA. After further examination, it was found that the above problem can be solved by setting the amount of crystallization at a specific temperature to an appropriate range.
[0010] The above problem is solved by providing any of the following [1] to [7].
[0011] [1] An optical polyvinyl alcohol film having a crystallization amount of 28 to 34% calculated by a relaxation curve obtained from pulsed NMR in heavy water at 30°C and a crystallization amount of 7 to 10% calculated by a relaxation curve obtained from pulsed NMR in heavy water at 70°C;
[0012] [2] An optical polyvinyl alcohol film as described in [1], wherein the difference between the amount of crystals calculated by the relaxation curve obtained from pulsed NMR in 50 ℃ heavy water and the amount of crystals calculated by the relaxation curve obtained from pulsed NMR in 70 ℃ heavy water is 11.5% or more;
[0013] [3] An optical polyvinyl alcohol film as described in [1] or [2], having a crystal weight of 29 to 33% as calculated by the relaxation curve obtained from pulsed NMR in heavy water at 30 ℃;
[0014] [4] An optical polyvinyl alcohol film described in any one of [1] to [3], wherein the difference between the amount of crystals calculated by the relaxation curve obtained from pulse NMR in 50 ℃ heavy water and the amount of crystals calculated by the relaxation curve obtained from pulse NMR in 70 ℃ heavy water is 14% or more;
[0015] [5] An optical polyvinyl alcohol film described in any one of [1] to [4], wherein the degree of polymerization of the polyvinyl alcohol included in the optical polyvinyl alcohol film is 3100 to 5000 or less;
[0016] [6] An optical polyvinyl alcohol film described in any one of [1] to [5], wherein the degree of saponification of the polyvinyl alcohol included in the optical polyvinyl alcohol film is 99.0% or higher;
[0017] [7] An optical polyvinyl alcohol film described in any one of [1] to [6], wherein the amount of plasticizer is 3 to 13 parts by mass per 100 parts by mass of polyvinyl alcohol contained in the optical polyvinyl alcohol film. Effects of the invention
[0018] By using the optical polyvinyl alcohol film of the present invention, in the manufacture of a polarizing film, there is no end folding during the stretching process, and no breakage occurs even when the stretching ratio is increased to a high magnification, thereby providing a PVA film capable of manufacturing a polarizing film with excellent optical performance. Specific details for implementing the invention
[0019] In this specification, a numerical range indicated using "~" implies that the values indicated before and after "~" are included as the lower and upper limits. Furthermore, in this specification, the upper and lower limits of a numerical range (content, physical properties, etc.) may be appropriately combined. In this specification, polyvinyl alcohol may be abbreviated as "PVA," and polyvinyl alcohol film may be abbreviated as "PVA film" or "film," respectively. MD refers to the machine direction in the manufacture of the polyvinyl alcohol film, and TD refers to the direction perpendicular to MD.
[0020] Generally, pulsed NMR is an analytical method for evaluating the molecular mobility of polymer materials, and from the analysis of PVA using pulsed NMR to date, it is known that components with low molecular mobility originate from crystals, components with medium molecular mobility originate from confined ranges, and components with high molecular mobility originate from ranges (Patent Documents 2, 3). Since pulsed NMR allows for the selection of conditions depending on the environment in which the polymer material is used, and the amount of crystals in the solid state can be obtained from solid NMR and the amount of crystals in the impregnated state of the solution can be obtained from solution NMR, information regarding the amount of crystals in the PVA film before and after stretching or during stretching is obtained by selecting the measurement conditions.
[0021] The inventors investigated in detail the relationship between the molecular mobility and crystallization amount of PVA during uniaxial stretching and the processability of stretching in the manufacture of a polarizer using pulsed NMR. As a result, it was found that the crystallization amount calculated by the relaxation curve obtained from pulsed NMR in heavy water at 30°C is related to the swelling process, dyeing process, and crosslinking process carried out in the first half of the polarizer manufacturing process, and the crystallization amount calculated by the relaxation curve obtained from pulsed NMR in heavy water at 70°C is related to the stretching process carried out in the second half of the polarizer manufacturing process. That is, if the crystallization amount is high during the swelling process, the film is conveyed as a relatively harder film than conventional films during swelling, making it difficult to bend and less likely to cause problems such as edge folding. In addition, if the crystallization amount is high during the dyeing process or the crosslinking process, the orientation of the iodine complex can be efficiently increased, thereby enabling the production of a polarizer film with high polarization performance. In addition, when the crystallization amount is relatively small during the stretching process, the film becomes softer and easier to stretch than conventional films, making high-magnification stretching possible and also making it difficult for stretching breakage to occur. In this way, when the crystallization amount at 30°C and 70°C satisfies a predetermined value, high polarization performance is exhibited, and the film becomes easy to process through stretching.
[0022] The optical polyvinyl alcohol film of the present invention has a crystallization amount of 28 to 34% calculated by the relaxation curve obtained from pulsed NMR in heavy water at 30°C. Since the crystallization amount is within this range, it is conveyed as a relatively rigid film during the swelling, dyeing, and crosslinking processes carried out throughout the manufacturing of polarizers, thus having the advantage of being difficult to bend and less likely to cause problems such as edge folding. The crystallization amount is preferably 29% or more, and may be 30% or 31% or more. On the other hand, the crystallization amount is preferably 33% or less. The crystallization amount calculated by the relaxation curve obtained from pulsed NMR in heavy water at 30°C can be measured by the method described in the examples.
[0023] The optical polyvinyl alcohol film of the present invention has a crystallization amount of 7 to 10 percent, calculated by a relaxation curve obtained from pulsed NMR in heavy water at 70°C. Since the crystallization amount is within this range, the film becomes soft and easy to stretch during the stretching process performed in the latter part of polarizer manufacturing, thereby enabling high-magnification stretching and having the advantage of being less prone to stretching fracture. The crystallization amount is preferably 7.5 percent or more, and may be 8 percent, 8.5 percent, or 9 percent or more. On the other hand, the crystallization amount is preferably 9.8 percent or less. The crystallization amount calculated by a relaxation curve obtained from pulsed NMR in heavy water at 70°C can be measured by the method described in the examples.
[0024] The optical polyvinyl alcohol film of the present invention preferably has a crystallization amount of 20 to 26% calculated by a relaxation curve obtained from pulsed NMR in heavy water at 50°C. The crystallization amount may be 21% or more. On the other hand, it is more preferable that the crystallization amount is 25% or less. The crystallization amount calculated by a relaxation curve obtained from pulsed NMR in heavy water at 50°C can be measured by the method described in the examples.
[0025] In addition, according to the inventors' investigation, it was found that it is important for the stretching process that the difference between the amount of crystals calculated by the relaxation curve obtained from pulse NMR in heavy water at 50°C and the amount of crystals calculated by the relaxation curve obtained from pulse NMR in heavy water at 70°C is greater than a certain value. Generally, the manufacture of a polarizing plate consists of a swelling process, a dyeing process, a crosslinking process, a stretching process, a washing process, and a drying process, and the process from swelling to crosslinking is carried out at approximately 30 to 50°C, and the stretching is carried out at approximately 50 to 70°C. Accordingly, it was found that it is ideal for the PVA film to have a relatively large amount of crystals in the temperature range from swelling to crosslinking so that it does not fold, and to have a relatively small amount of crystals in the temperature range of the stretching process so that it has softness suitable for high-magnification stretching and does not melt. Based on that, at 50 to 70°C, it is desirable for the crystallization amount to be significantly reduced to the extent that it does not melt, in order to increase elongation. Specifically, it is desirable that the difference between the crystallization amount calculated by the relaxation curve obtained from pulse NMR in heavy water at 50°C and the crystallization amount calculated by the relaxation curve obtained from pulse NMR in heavy water at 70°C is 10% or more, more desirable that it is 11.5% or more, even more desirable that it is 12% or more, and it may be 13% or more or 14% or more. In addition, the difference in crystallization amount is typically 19% or less.
[0026] Regarding the optical polyvinyl alcohol film of the present invention, methods for controlling the crystallization amount at each temperature to a predetermined range include adjusting the molecular weight or degree of saponification of PVA, washing PVA to improve purity, introducing a modifier group into PVA, controlling the degree of crystallization or orientation state of the polymer during the process of forming a film from an aqueous PVA solution, and controlling the drying state of the film during and after forming. Among these, it is known that the method of adjusting the molecular weight or degree of saponification of PVA and the method of controlling the degree of crystallization or orientation state of the polymer during the process of forming a film from an aqueous PVA solution contribute significantly to the control of the crystallization amount of PVA and is preferred.
[0027] [Polyvinyl alcohol]
[0028] As for the PVA included in the optical polyvinyl alcohol film of the present invention, examples include those obtained by saponifying a polyvinyl ester obtained by polymerizing one or more vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pivalate, vinyl versatate, vinyl laurate, vinyl stearate, vinyl benzoate, and isopropene acetate. Among the above vinyl esters, vinyl acetate is preferred in terms of ease of manufacturing polyvinyl alcohol, ease of availability, and cost.
[0029] PVA may be modified by one or more copolymerizable monomers, provided that the effects of the present invention are not impaired. Examples of such copolymerizable monomers include unsaturated carboxylic acids or derivatives thereof; unsaturated sulfonic acids or derivatives thereof; and α-olefins having 2 to 30 carbon atoms. The proportion of structural units derived from copolymerizable monomers in PVA is preferably 5 mol% or less, based on the total number of moles of structural units constituting PVA.
[0030] The degree of polymerization of PVA is preferably 3,100 or higher, and more preferably 3,200 or higher. If the degree of polymerization is less than 3,100, it becomes difficult to satisfy both ranges of crystallization amount at 30°C and 70°C of the PVA film of the present invention. The degree of polymerization of PVA is preferably 5,000 or lower, more preferably 4,000 or lower, and even more preferably 3,500 or lower. If the degree of polymerization is 4,000 or lower, the PVA used as a raw material can be manufactured industrially without problems based on conventional technology, thus allowing for the compatibility of productivity. Furthermore, the degree of polymerization of PVA refers to the average degree of polymerization measured in accordance with the specifications of JIS K6726-1994.
[0031] From the perspective of controlling the crystallization amount at 30°C and 70°C, the degree of saponification of PVA is preferably 98.0 mol% or higher, more preferably 99.0 mol% or higher, even more preferably 99.4 mol% or higher, and particularly preferably 99.8 mol% or higher. If the degree of saponification is less than 98.0 mol%, there is a risk that the crystallization amount will be reduced. In this specification, the degree of saponification of PVA refers to the ratio (mol%) of the moles of said vinyl alcohol units to the total moles of said vinyl alcohol units and said vinyl alcohol units, which are structural units (typically vinyl ester units) that can be converted into vinyl alcohol units by saponification, possessed by PVA. The degree of saponification can be measured in accordance with the description in JIS K6726-1994.
[0032] [Plasticizer]
[0033] The optical polyvinyl alcohol film of the present invention may contain a plasticizer. Examples of plasticizers include polyhydric alcohols such as ethylene glycol, glycerin, propylene glycol, diethylene glycol, diglycerin, triethylene glycol, tetraethylene glycol, and trimethylolpropane, and the PVA film of the present invention may contain one or more of these plasticizers. Among these, glycerin is preferred in terms of its effect of improving stretchability.
[0034] When an optical polyvinyl alcohol film contains a plasticizer, the content of the plasticizer is preferably 3 to 13 parts by mass per 100 parts by mass of polyvinyl alcohol. The upper limit of the plasticizer content is more preferably 12 parts by mass, and 11 parts by mass may also be used. The lower limit of the plasticizer content is more preferably 5 parts by mass, even more preferably 8 parts by mass, and 9 parts by mass may also be used. If the plasticizer content exceeds 13 parts by mass, the mobility of PVA is significantly improved, making it prone to excessive crystal growth, and the crystals tend to coarsen. Conversely, if the plasticizer content is less than 3 parts by mass, the mobility of PVA is excessively reduced, making it difficult to grow crystals, and the crystal content tends to decrease. In this case, in addition to the deterioration of the productivity of the PVA film, there is a risk of elongation fracture as the film becomes high-tensile during stretching processing.
[0035] [Surfactant]
[0036] The optical polyvinyl alcohol film of the present invention may include a surfactant. By manufacturing a PVA film using a film-forming stock solution containing a surfactant, the film-forming properties of the PVA film are improved. As a result, the occurrence of non-uniformity in the thickness of the PVA film is suppressed, and the peeling of the PVA film from the metal roll or belt used for film formation becomes easier. When manufacturing a PVA film from a film-forming stock solution containing a surfactant, the surfactant is contained in the resulting PVA film.
[0037] The type of surfactant is not particularly limited, but anionic surfactants and nonionic surfactants are preferred from the perspective of peelability of the PVA film from a metal roll or belt.
[0038] Anionic surfactants are preferably carboxylic acid types such as potassium laurate; sulfate ester types such as polyoxyethylene lauryl ether sulfate and octyl sulfate; and sulfonic acid types such as dodecylbenzene sulfonate.
[0039] As nonionic surfactants, for example, alkyl ether type such as polyoxyethylene oleyl ether; alkylphenyl ether type such as polyoxyethylene octylphenyl ether; alkyl ester type such as polyoxyethylene laurate; alkylamine type such as polyoxyethylene laurylamino ether; alkylamide type such as polyoxyethylene lauric acid amide; polypropylene glycol ether type such as polyoxyethylene polyoxypropylene ether; alkanolamide type such as lauric acid diethanolamide, oleic acid diethanolamide; and allylphenyl ether type such as polyoxyalkylene allylphenyl ether are preferred.
[0040] These surfactants may be used as a single type or in combination of two or more types.
[0041] When the optical polyvinyl alcohol film of the present invention contains a surfactant, the lower limit of the surfactant content is preferably 0.01 parts by mass per 100 parts by mass of PVA, more preferably 0.02 parts by mass, and even more preferably 0.03 parts by mass. By making the surfactant content greater than or equal to the above lower limit, the film-forming and peelability of the PVA film are further improved. Meanwhile, the upper limit of the surfactant content in the PVA film is preferably 0.5 parts by mass per 100 parts by mass of PVA, more preferably 0.3 parts by mass, and even more preferably 0.2 parts by mass. By making the surfactant content less than or equal to the above upper limit, it is possible to suppress the surfactant from bleeding out onto the surface of the PVA film, causing blocking, and reducing handling performance.
[0042] [Other ingredients]
[0043] The optical polyvinyl alcohol film of the present invention may additionally contain, in addition to PVA, a plasticizer, and a surfactant, components such as an antioxidant, an antifreeze, a pH adjuster, an anticoloring agent, and an emulsion, as needed. The ratio of the total mass of PVA, the surfactant, and the plasticizer to the total mass of the PVA film is preferably 60 to 100 mass%, more preferably 80 to 100 mass%, and even more preferably 90 to 100 mass%.
[0044] [Shape, etc.]
[0045] The shape of the optical polyvinyl alcohol film of the present invention is not particularly limited, but it is preferable that it be a long film. This allows for the continuous and easy production of a more uniform film, and also enables continuous use in cases such as manufacturing a polarizing film using it. The length (length in the longitudinal direction) of the long film is not particularly limited and can be appropriately set according to the application, for example, within the range of 5 to 30,000 m. Among these, the length of the optical polyvinyl alcohol film is preferably 100 m or more, and more preferably 1,000 m or more.
[0046] The width of the optical polyvinyl alcohol film of the present invention is not particularly limited, but may be 3,000 mm or more, or 4,000 mm or more. Typically, the width of the optical polyvinyl alcohol film is 10,000 mm or less.
[0047] The thickness of the optical polyvinyl alcohol film of the present invention is preferably 20 to 65 μm. If the thickness is less than 20 μm, handling properties during stretching deteriorate, and if the thickness is greater than 65 μm, it is not desirable as a polarizing plate for a thin display.
[0048] [Method for manufacturing PVA film]
[0049] The optical polyvinyl alcohol film of the present invention may be manufactured using known methods. Any method may be employed, such as a flexible film-forming method, a wet film-forming method (extrusion into a solvent-free solution), a dry-wet film-forming method, a gel film-forming method (a method of obtaining a PVA film by first cooling and gelling the film-forming solution and then extracting and removing the solvent), or a combination thereof, by using a film-forming solution homogenized by adding a solvent, additives, etc., to PVA, or a melt extrusion film-forming method or an inflation molding method in which the film-forming solution is obtained using an extruder, etc., and then extruded through a T-die, etc. Among these, the flexible film-forming method is preferred because it allows for obtaining a homogeneous film along the width direction with good productivity. The flexible film-forming method for PVA films will be described below.
[0050] The flexible film formation method for PVA films is divided into a flexible process, a drying process, and a heat treatment process, and is carried out in this order.
[0051] · Flexible process
[0052] In the flexibleing process, first, a film-forming solution containing PVA, a solvent, and additives such as a plasticizer as needed is prepared. Next, this film-forming solution is flexible (supplied) into a film shape onto a support of a drying roll, drying drum, or drying belt (hereinafter referred to as a support such as a drying roll). As a result, a liquid film of the film-forming solution is formed on the support.
[0053] In the flexibility process, the surface temperature of the support that flexes the film-forming solution is preferably in the range of 65 to 120°C. If the surface temperature is excessively high, bubbles will form, leading to a deterioration of the film surface. Also, if the temperature is excessively low, it will not dry sufficiently. Regarding the optical polyvinyl alcohol film of the present invention, although not limited in any way, if the surface temperature of the support that flexes the film-forming solution is 90 to 100°C, it is easy to manufacture the optical polyvinyl alcohol film of the present invention.
[0054] The film-forming solution generally passes through the die lip of a die, such as a T-die, and is formed into a film on a support, such as a drying roll. On the support, the solvent volatilizes from the side of the formed film that is not in contact with the support (hereinafter referred to as the free side), while substantially not volatilizing from the side that is in contact with the support (hereinafter referred to as the touch side). Consequently, a distribution is formed in which the solvent concentration is lower on the free side and higher on the touch side in the direction of the film thickness. Therefore, the solidification of PVA proceeds first from the free side.
[0055] In order to control the crystallization amount contained in the optical polyvinyl alcohol film of the present invention, it is important to adjust the conditions of the roll temperature of the flexible process, the temperature and humidity of the film-making environment, the contact time with the roll, the moisture content of the film during film-making, and the roll temperature of the drying process and the heat treatment process. In addition, the control of the crystallization amount is influenced by the degree of polymerization of PVA, the degree of saponification of PVA, and the content of the plasticizer as described above, as well as the moisture content of the film-making solution and the heating temperature, so these factors are added to control the crystallization amount.
[0056] The moisture content of the film-forming solution used in the flexibility process is approximately 60 to 95 mass%. The moisture content of the liquid film after peeling from the flexibility process is selected to be approximately 5 to 40 mass%, and depending on other conditions, if it is approximately 11 to 16 mass%, it is easy to manufacture the optical polyvinyl alcohol film of the present invention.
[0057] In this specification, the moisture content of the liquid film or polyvinyl alcohol film refers to the value obtained by the following formula (1).
[0058] Moisture content of membrane-removing solution (mass%)
[0059] ={(Wc-Wd) / Wc}×100 (1)
[0060] In the above formula (1), Wc represents the mass (g) of a sample taken from the film-making solution, and Wd represents the mass (g) of the sample Wc (g) when dried for 16 hours in an electric dryer at a temperature of 105°C.
[0061] In addition, the moisture content of the liquid film after peeling from the support in the flexible process can be adjusted by changing the peripheral speed of the support. For example, if the peripheral speed of the support is slow, the time the liquid film is in contact with the support increases, so the moisture content of the PVA film when peeling from the support can be reduced, and typically, the peripheral speed of the support is selected to be about 8 to 30 m / min. If the peripheral speed of the support is within the above range, a PVA film having a desired crystallization amount can be manufactured while maintaining the productivity of the PVA film.
[0062] · Drying process
[0063] The draw ratio between supports in the drying process is appropriately selected depending on the properties of the PVA used or the conditions of the flexibility process. Methods for drying the liquid film include heating the support itself to a high temperature using a heat transfer medium, or blowing hot air onto the surface opposite to the side of the liquid film in contact with the support. For stretching the dried film, methods include using multiple supports and controlling the peripheral speed of each support.
[0064] · Heat treatment process
[0065] In the heat treatment process, the film peeled from a support such as a drying roll of the above drying process is conveyed to a support of a heat treatment roll, heat treatment drum, or heat treatment belt (hereinafter referred to as a support such as a heat treatment roll) and heat-treated on the support. Examples of methods for heat-treating the film include heating the support itself to a high temperature using a heat medium, blowing hot air onto the opposite side of the surface in contact with the support of the liquid film, or using a drying oven.
[0066] The method of heat treatment is not particularly limited and may include methods such as blowing hot air with a floating dryer, irradiating near-infrared rays with an infrared lamp, or contacting with a heat treatment roll; however, to obtain the PVA film of the present invention, it is preferable to directly contact the surface of the PVA film with the heat treatment roll. Furthermore, when drying the PVA film using a plurality of heat treatment rolls, it is preferable to alternately contact one surface of the PVA film with the other surface of the heat treatment roll. This allows the degree of crystallization on both sides of the PVA film to be increased evenly. In this case, the number of heat treatment rolls is preferably two or more, and more preferably four or more.
[0067] The moisture content of the PVA film when it is brought into contact with the first support in the heat treatment process is about 1 to 13 mass%. By keeping the moisture content of the PVA film when it is brought into contact with the first heat treatment roll within the above range, changes in orientation during stretching are suppressed, making it easier to suppress film breakage.
[0068] The surface temperature of the support for performing heat treatment is preferably selected in the range of 80 to 130°C. By keeping the surface temperature of the support within the above range, it becomes possible to manufacture a PVA film having a desired amount of crystals.
[0069] [Method for manufacturing polarizing film and polarizing plate]
[0070] A known method may be employed as a method for manufacturing a polarizing plate using the optical polyvinyl alcohol film of the present invention. Generally, a protective film is attached to a polarizing film obtained by stretching a PVA film to form a polarizing plate. The polarizing film is manufactured by unwinding a polyvinyl alcohol film and undergoing a swelling process, a dyeing process, a crosslinking process, a stretching process, a washing process, a drying process, etc.
[0071] The swelling process is a process of immersing a PVA film in water. The temperature of the water when immersed is approximately 15 to 45°C, and the immersion time in the swelling bath is approximately 0.1 to 10 minutes. In addition, the water used for immersion is not limited to pure water; it may be an aqueous solution in which various components are dissolved, or a mixture of water and a water-soluble medium. Furthermore, if necessary, a stretching operation may be performed during the process.
[0072] The dyeing process is a process in which a PVA film is immersed in a solution (especially an aqueous solution) containing iodine and potassium iodide as a dyeing bath. The concentration of iodine in the dyeing bath is approximately 0.01 to 0.5 mass%, and the concentration of potassium iodide is approximately 0.01 to 10 mass%. The temperature of the dyeing bath is approximately 20 to 50 ℃. The immersion time is approximately 0.5 to 3 minutes. Additionally, if necessary, a stretching operation may be performed during the process. Generally, the dyeing process is formed after the swelling process and before the crosslinking process.
[0073] The crosslinking process is a process of immersing a PVA film in an aqueous solution containing a crosslinking agent. When crosslinking treatment is performed, a crosslinked structure is introduced into the PVA film, which effectively prevents the leaching of PVA into water when a relatively high-temperature and wet stretching treatment is performed. As the crosslinking agent, one or more types of boron compounds, such as borates like borax, may be used in addition to boric acid. The concentration of the crosslinking agent in the aqueous solution containing the crosslinking agent is approximately 1 to 15 mass%, and a crosslinking aid such as potassium iodide may be used in combination if necessary. The temperature of the aqueous solution containing the crosslinking agent is approximately 20 to 50°C. Additionally, if necessary, a stretching operation may be performed during the treatment. Generally, the crosslinking process is formed after the dyeing process and before the stretching process.
[0074] In the stretching process, a wet stretching method in an aqueous solution is generally used, and the PVA film is stretched 2 to 5 times in one axial direction in the aqueous solution. The temperature during stretching is approximately 20 to 70°C. The aqueous solution used in the stretching process may contain boric acid, etc., as necessary. In addition, the stretching operation may be performed not only in a single step but also in stages to match the above ratio. The above aqueous solution may contain boric acid. Generally, the concentration of boric acid in the aqueous solution is approximately 0.5 to 6.0 mass%. Furthermore, the aqueous solution may contain potassium iodide, and it is preferable that the concentration be within the range of 0.01 to 10 mass%.
[0075] The washing process is generally formed after the stretching process and before the drying process. In addition to boric acid, the aqueous solution used in the washing bath may contain iodine compounds or metal compounds as needed. The concentration of boric acid is about 1 to 15 mass%, and the iodine compound is about 0.01 to 10 mass%. The temperature of the washing bath is about 15 to 60 ℃.
[0076] The drying treatment in the drying process is generally carried out at 30 to 150°C.
[0077] The total stretching ratio (total stretching ratio) of the entire stretching process can be appropriately set according to the desired polarization performance or polarizing film width, and is usually about 5 to 6 times.
[0078] There are no specific limitations on the film thickness of the polarizing film, and it can be, for example, 30 μm or less, or furthermore, 25 μm or less. From the perspective of reducing shrinkage stress of the polarizing film and, furthermore, the polarizing plate using it, and preventing the laminated thin glass from bending, it is preferable that the film thickness of the polarizing film be 20 μm or less, and more preferable that it be 15 μm or less. On the other hand, since a polarizing film that is too thin tends to be difficult to manufacture or handle, it is preferable that the film thickness of the polarizing film be 3 μm or more.
[0079] [Polarizing plate]
[0080] A polarizing film manufactured using the optical polyvinyl alcohol film of the present invention is used as a polarizing plate by laminating a protective film that is optically transparent and also possesses mechanical strength. Since the polarizing plate has high polarization performance derived from the polarizing film of the present invention, the polarizing plate is also an embodiment of the present invention. As the protective film, cellulose triacetic acid (TAC) film, cellulose acetic acid-butyric acid (CAB) film, acrylic film, polyester film, etc., are used. In addition, as the adhesive for lamination, PVA-based adhesives or urethane-based adhesives may be used, but among these, PVA-based adhesives are preferred.
[0081] The polarizing plate obtained as described above can be used as a component of an LCD by coating it with an adhesive such as an acrylic-based adhesive and then laminating it onto a glass substrate. At the same time, it may also be laminated with a phase difference film, a viewing angle enhancement film, a brightness enhancement film, etc.
[0082] Examples
[0083] The present invention will be specifically explained below by way of examples, but the present invention is not limited in any way by these examples. Each evaluation method employed in the examples and comparative examples is shown below.
[0084] <Measurement of Crystal Amount Using Pulsed NMR>
[0085] 50 mg of PVA film cut to 10 mm × 5 mm was weighed, immersed in 5 g of heavy water, and heated with a block heater at each measurement temperature (30 ℃, 50 ℃, 70 ℃) for 2 hours. Afterward, the entire amount of film and 0.95 g of heavy water were placed in a sample tube, and under the following conditions 1 The spin-spin relaxation time T2 of H was measured.
[0086] · Measurement conditions
[0087] Device: Minispec mq20+AS (Bruker)
[0088] Pulse Series: Solid-Echo Method
[0089] Observation nucleus : 1 H
[0090] Measurement temperature: 30 ℃, 50 ℃, 70 ℃
[0091] Scan count: 304
[0092] Pulse repetition time: 1s
[0093] Dummy shots: 4 times
[0094] Observation time: 6 ms (30, 50 ℃), 7 ms (70 ℃)
[0095] · Interpretation method
[0096] The obtained T2 relaxation curve was linearly least squares fitted using the following formula to calculate the crystallized amount (a1), constrained non-crystallized amount (a2), non-crystallized amount (a3), relaxation time of the crystallized component (tau1), relaxation time of the constrained non-crystallized component (tau2), relaxation time of the non-crystallized component (tau3), and integer a0 in the PVA film.
[0097] Intensity = a0+a1×exp(-0.5×(t / tau1)2)+a2×exp(-1 / 1.4×(t / tau2)1.4)+a3×exp(-t / tau3)
[0098] In the present invention, the ratio (%) of each component to the sum (a1 + a2 + a3) of a1, a2, and a3 derived from the above formula is defined as the determined amount (A1), the constrained non-determined amount (A2), and the non-determined amount (A3), respectively. For example, the value of the determined amount (A1) is expressed as a1 / (a1 + a2 + a3) × 100.
[0099] <Folded edge>
[0100] In the following examples and comparative examples, polarizing films were manufactured by changing the stretching ratio during swelling treatment to 1.20 times, the stretching ratio during dyeing treatment to 1.26 times, the stretching ratio during crosslinking treatment to 2.00 times, and the stretching ratio during stretching treatment to 2.00 times, and whether folding occurred at the ends of the PVA film after swelling treatment was evaluated visually. Folding occurred at both ends as “C,” folding occurred at one side as “B,” and no folding occurred as “A.”
[0101] <Number of fractures>
[0102] In the following examples or comparative examples, the manufacturing of the polarizing film was carried out continuously for 8 hours, and the number of times the PVA film broke during that time was measured.
[0103] <Single Transmittance and Polarization Degree>
[0104] A rectangular sample measuring 4 cm in the MD direction × 2 cm in the TD direction of the polarizing film was taken from the center of the TD direction of the polarizing film, and the parallel transmittance and cross-Nicole transmittance of the polarizing film were measured using an integrating sphere-equipped spectrophotometer V-7100 (manufactured by Nippon Spectrophoto Co., Ltd.) and an automatic polarizing film measuring device VAP-7070S (manufactured by Nippon Spectrophoto Co., Ltd.) equipped with a Glen Taylor polarizing film. Here, the measurement wavelength range was set to 380 to 780 nm, and the transmittance when the vibration direction of the polarizing light incident on the polarizing film through the Glen Taylor polarizing film was parallel to the transmission axis of the polarizing film was defined as parallel transmittance, and the transmittance when it was perpendicular to the transmission axis of the polarizing film was defined as cross-Nicole transmittance. Afterwards, using the “Polarizing Film Evaluation Program” (manufactured by Nippon Spectroscopic Co., Ltd.), visual sensitivity correction was performed in the visible light region of a 2° field of view with a C light source using the aforementioned parallel transmittance and cross-Nicole transmittance in accordance with JIS Z 8722 (Method for Measuring Object Color), and the single transmittance and degree of polarization of the polarizing film were calculated, and these two values were obtained as the optical characteristics of the polarizing film.
[0105] [Example 1]
[0106] 100 parts by mass of PVA (degree of saponification 99.9 mol%, degree of polymerization 3,300), 10.0 parts by mass of glycerin as a plasticizer, 0.04 parts by mass of lauric acid diethanolamide as a surfactant, and 253 parts by mass of water were melt-mixed using a melt extruder to prepare a film-forming solution with a moisture content of 72.5 mass%. Subsequently, the obtained film-forming solution was extruded in the form of a film from a T-die onto the first support (drying roll) (surface temperature 94 ℃) of a film-forming device equipped with a plurality of supports (drying rolls or heat treatment rolls) having rotation axes parallel to each other to form a liquid film, and the liquid film was dried until the moisture content of the liquid film became 13 mass% (flexing process). That is, the moisture content of the liquid film after the flexing process was 13 mass%. Subsequently, a liquid film was peeled off from the first drying roll, and a drying process or a heat treatment process was performed such that the contact surface of the liquid film with the first drying roll and the non-contact surface with the first drying roll alternately faced each drying roll or heat treatment roll. Specifically, first, the liquid film obtained from the softening process was dried on at least three supports (drying rolls) (surface temperature 95°C) until the moisture content of the liquid film became 10 mass% (drying process). That is, the moisture content of the liquid film after the drying process was 10 mass%. Subsequently, the liquid film obtained from the drying process was heat-treated on at least two supports (heat treatment rolls) (surface temperature 80 to 120 °C) until the moisture content of the liquid film became 8 mass% (heat treatment process), thereby producing a polyvinyl alcohol film (film thickness 45 μm, width 4500 mm, length 1000 m). That is, the moisture content of the polyvinyl alcohol film after the heat treatment process was 7 mass%. A 500 m slit was made in the obtained polyvinyl alcohol film with a width of 650 mm so that the center of the PVA film in the width direction before and after the slit coincided, thereby obtaining a PVA film for stretching.In addition, for the PVA film for stretching, the amount of crystals in heavy water at 30 ℃, 50 ℃, and 70 ℃ was determined using the method described in the above “Measurement of amount of crystals using pulsed NMR.” The results are shown in Table 1.
[0107] A polarizing film was continuously manufactured by performing swelling treatment, dyeing treatment, crosslinking treatment, stretching treatment, washing treatment, and drying treatment in this order on the PVA film for stretching obtained in Example 1. The swelling treatment was performed by uniaxially stretching the film 2.00 times in the longitudinal direction while immersing it in pure water (swelling treatment solution) at 25°C. The dyeing treatment was performed by uniaxially stretching the film 1.26 times in the longitudinal direction while immersing it in a potassium iodide / iodine aqueous dyeing solution (dyeing treatment solution) at a temperature of 32°C (potassium iodide / iodine (mass ratio) 23, iodine concentration 0.03 to 0.05 mass%). In this dyeing treatment, the iodine concentration in the dyeing solution was adjusted to a range of 0.03 to 0.05 mass% so that the single transmittance of the resulting polarizing film is in the range of 43.5% ± 0.2%. The crosslinking treatment was carried out by immersing the material in an aqueous boric acid solution (crosslinking treatment solution) (boric acid concentration 2.6 mass%) at 32°C and uniaxially stretching it 1.19 times in the longitudinal direction. The stretching treatment was carried out by immersing the material in an aqueous boric acid / potassium iodide solution (stretching treatment solution) (boric acid concentration 2.8 mass%, potassium iodide concentration 5 mass%) at 58.5°C and uniaxially stretching it 2.00 times in the longitudinal direction. The cleaning treatment was carried out by immersing the sample in a potassium iodide / boric acid aqueous solution (cleaning treatment solution) at 22°C (potassium iodide concentration 3 to 6 mass%, boric acid concentration 1.5 mass%) for 12 seconds without stretching. Afterwards, the first drying step was performed in a dryer at 50°C, and the second drying step was performed in a dryer at 60°C to obtain a polarizing film.
[0108] [Example 2]
[0109] A polarizing film was obtained in the same manner as in Example 1, except that the moisture content of the liquid film after the flexibility process was changed to 5 mass%. The results are shown in Table 1.
[0110] [Example 3]
[0111] A polarizing film was obtained in the same manner as in Example 1, except that the moisture content of the liquid film after the flexibility process was changed to 5 mass% and the amount of plasticizer was changed to 12.0 mass parts. The results are shown in Table 1.
[0112] [Example 4]
[0113] A polarizing film was obtained in the same manner as in Example 1, except that the degree of polymerization of PVA was 3,480, glycerin was 12.0 parts by mass as a plasticizer, the moisture content of the film-making solution was 72.7 mass%, the surface temperature of the initial support (drying roll) of the film-making device was 90°C, the surface temperature of the support (drying roll) during the drying process was 75 to 90°C, and the surface temperature of the support (heat treatment roll) during the heat treatment process was 60 to 125°C. The results are shown in Table 1. In addition, the liquid film after peeling from each roll is different from Example 1 because it depends on the surface temperature of each roll.
[0114] [Comparative Example 1]
[0115] 100 parts by mass of PVA (degree of saponification 99.3 mol%, degree of polymerization 3,040), 10.0 parts by mass of glycerin as a plasticizer, 0.12 parts by mass of lauric acid diethanolamide as a surfactant, and 233 parts by mass of water were melt-mixed using a melt extruder to prepare a film-forming solution with a moisture content of 71.0 mass%. Subsequently, the obtained film-forming solution was extruded as a film from a T-die onto the first support (drying roll) (surface temperature 94 ℃) of a film-forming device equipped with a plurality of supports (drying rolls or heat treatment rolls) having rotation axes parallel to each other to form a liquid film, and the liquid film was dried until the moisture content of the liquid film became 16 mass% (flexing process). That is, the moisture content of the liquid film after the flexing process was 16 mass%. Subsequently, a liquid film was peeled off from the first drying roll, and a drying process or a heat treatment process was performed such that the contact surface of the liquid film with the first drying roll and the non-contact surface with the first drying roll alternately faced each drying roll or heat treatment roll. Specifically, first, the liquid film obtained from the softening process was dried on at least three supports (drying rolls) (surface temperature 95°C) until the moisture content of the liquid film became 10 mass% (drying process). That is, the moisture content of the liquid film after the drying process was 10 mass%. Subsequently, the liquid film obtained from the drying process was heat-treated on at least two supports (heat treatment rolls) (surface temperature 80 to 120 °C) until the moisture content of the liquid film became 8 mass% (heat treatment process), thereby producing a polyvinyl alcohol film (film thickness 45 μm, width 4500 mm, length 1000 m). That is, the moisture content of the polyvinyl alcohol film after the heat treatment process was 7 mass%. A 500 m slit was made in the obtained polyvinyl alcohol film with a width of 650 mm so that the center of the PVA film in the width direction before and after the slit coincided, thereby obtaining a PVA film for stretching.In addition, for the PVA film for stretching, the amount of crystals in heavy water at 30°C, 50°C, and 70°C was determined using the method described in "Measurement of amount of crystals using pulsed NMR" above. The results are shown in Table 1. The manufacturing of the polarizing film was carried out in the same manner as in Example 1.
[0116] [Comparative Example 2]
[0117] A polarizing film was obtained in the same manner as Comparative Example 1, except that the moisture content of the liquid film after the flexibility process was changed to 18 mass%. The results are shown in Table 1.
[0118] [Comparative Example 3]
[0119] A polarizing film was obtained in the same manner as Comparative Example 1, except that the amount of plasticizer was changed to 12.0 parts by mass. The results are shown in Table 1.
[0120] [Comparative Example 4]
[0121] A polarizing film was obtained in the same manner as Comparative Example 1, except that the degree of saponification of PVA was 99.9 mol%, the degree of polymerization of PVA was 3,480, glycerin was used as a plasticizer in an amount of 12.0 mass parts, the moisture content of the film-making solution was 73.3 mass%, and the surface temperature of the support (heat treatment roll) in the heat treatment process was 60 to 125 ℃. The results are shown in Table 1. In addition, the liquid film after peeling from each roll is different from Comparative Example 1 because it depends on the surface temperature of each roll.
[0122] [Comparative Example 5]
[0123] A polarizing film was obtained in the same manner as Comparative Example 1, except that the degree of saponification of PVA was 99.9 mol%, the degree of polymerization of PVA was 3,480, glycerin was used as a plasticizer in an amount of 12.0 mass parts, the moisture content of the film-making solution was 72.1 mass%, the surface temperature of the initial support (drying roll) of the film-making device was 95 ℃, and the surface temperature of the support (heat treatment roll) in the heat treatment process was 60 to 120 ℃. The results are shown in Table 1. In addition, the liquid film after peeling from each roll is different from Comparative Example 1 because it depends on the surface temperature of each roll.
[0124]
Claims
Claim 1 An optical polyvinyl alcohol film having a crystallization amount of 28 to 34% calculated by a relaxation curve obtained from pulsed NMR in heavy water at 30°C and a crystallization amount of 7 to 10% calculated by a relaxation curve obtained from pulsed NMR in heavy water at 70°C. Claim 2 An optical polyvinyl alcohol film according to claim 1, wherein the difference between the amount of crystals calculated by the relaxation curve obtained from pulsed NMR in heavy water at 50°C and the amount of crystals calculated by the relaxation curve obtained from pulsed NMR in heavy water at 70°C is 11.5% or more. Claim 3 An optical polyvinyl alcohol film according to claim 1 or 2, wherein the crystal weight calculated by the relaxation curve obtained from pulsed NMR in heavy water at 30°C is 29 to 33%. Claim 4 An optical polyvinyl alcohol film according to claim 1 or 2, wherein the difference between the amount of crystals calculated by the relaxation curve obtained from pulsed NMR in heavy water at 50°C and the amount of crystals calculated by the relaxation curve obtained from pulsed NMR in heavy water at 70°C is 14% or more. Claim 5 An optical polyvinyl alcohol film according to claim 1 or 2, wherein the degree of polymerization of the polyvinyl alcohol included in the optical polyvinyl alcohol film is 3100 to 5000 or less. Claim 6 An optical polyvinyl alcohol film according to claim 1 or 2, wherein the degree of saponification of the polyvinyl alcohol included in the optical polyvinyl alcohol film is 99.0% or higher. Claim 7 An optical polyvinyl alcohol film according to claim 1 or 2, wherein the amount of plasticizer is 3 to 13 parts by mass per 100 parts by mass of polyvinyl alcohol contained in the optical polyvinyl alcohol film.
